Edukasi Stunting pada Kelompok Anak Melalui Poster dengan Menggunakan Kalimat Persuasif di Kelurahan Mompang Jae Kabupaten Mandailing Natal - Abdul Azis Nasution; Nikmah Sari Hasibuan; Husniah Ramadhani Pulungan; Khatib Lubis; Nur Afifah; Eli Marlina Harahap (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
Stunting education is crucial for children to grasp the perils of stunting and uphold their health and well-being. Educating children about this matter is challenging, given their susceptibility to boredom and difficulty in comprehending complex concepts. Innovative approaches are essential to captivate their attention and facilitate comprehension. In Mompang Jae Village, Mandailing Natal Regency, stunting education was conducted for a cohort of children using persuasive posters and videos. The study involved 30 child participants, employing a persuasive educational method. The percentage of respondents with limited knowledge plummeted from 67% to 33%, while those with a strong grasp of the topic surged from 17% to 67%. Effective knowledge enhancement can be achieved through diverse methods, including education. Incorporating visually appealing educational aids, such as persuasive posters, aids information absorption due to their visually intuitive nature. These posters are prominently displayed at the local healthcare center (posyandu), designed to engage children's attention and reinforce the significance of combating stunting. Keywords: Education, Stunting, Persuasive Poster.